Pengusaha Telur Asin di Kelurahan Sisir di Kota Batu Sebagai Upaya Peningkatan Pendapatan Masyarakat - Muslichah Muslichah; Hedher Tuakia (Jurnal ABM Mengabdi, 2018)
Along with the rapid development of the city of Batu to support tourist areas, there are growing culinary stalls, restaurants and hotels in the city of Batu. This opens up business opportunities for residents of Batu, one of which is by making salted eggs as snacks that can be processed with various creations by several stalls or restaurants, such as salted egg botok, salted egg gurami, fried salted sambal, salted egg sauce for various variations fish dishes, salted fried tofu and others. In addition, there are also many duck farmers in the city of rock, so the raw material in the form of duck eggs is very abundant. The problem faced by partners is the lack of available tools that support the production process, namely: (1) mixing bricks, salt and water powder, (2) gas stoves and pots for boiling salted eggs are still very limited, and (3) blenders for remove the grasak salt (4) where the eggs are cooked, (5) the bucket used is limited in capacity, (6) the table has limited capacity. In addition, in terms of management, partners lack understanding about financial reports and marketing management. The expected outcomes are community service reports, national-scale journals and print media. It is hoped that with the development of this business, it will help local communities to improve their opinions